Special Basic Education Center for Children and Adolescents with Disabilities in the City of Tacna - Zambrano Guerrero, Lourdes (2015)
Objective: Propose and develop the architectural project of a Special Basic Education Center for the comprehensive training of children and adolescents with disabilities in the city of Tacna, as a solution to the problem of the lack of adequate infrastructure, in order to provide educational spaces of optimum quality being complemented with environments related to the processes of diagnosis, treatment and job training. Methodology: The descriptive methodology was applied for the information and data collection stage until a diagnosis was obtained; and the experimental one to propose an adequate special educational infrastructure. Finally, inspections were carried out to the existing special basic education centers, bibliographic exploration, photographic record and cases of reliable projects, the location criteria and designs for special education centers were also used, a tool that allowed the selection of the architectural terrain. Results: As a result of the diagnosis and according to the analysis of the population growth with disabilities in the city of Tacna, the formulation of the special basic education center was considered very necessary because it will contribute to the level of care, support and advice to students with special needs, generating scenarios that stimulate and / or structure social activities from an individual and collective point of view. Conclusions: The projection of a special educational infrastructure will achieve compliance with the standards of quality, safety and regulations, these standards must recognize the right that children and adolescents have to an education that considers and respects the different capacities and educational needs, establishing a plan to organize and develop management processes to improve the quality of student learning.